The minders - Marrs, John (Freelance journalist) (Berkley, 2021)
"The new high concept thriller from the author of The Passengers and the word-of-mouth sensation The One, soon to be a Netflix original series. In the 21st century, information is king. But computers can be hacked and files can be broken into - so a unique government initiative has been born. Five ordinary people have been selected to become "minders" - the latest weapon in thwarting cyberterrorism. Transformed by a revolutionary medical procedure, the country's most classified information has been taken offline and turned into genetic code implanted inside their heads. Together, the five know every secret - the truth behind every government lie, conspiracy theory and cover up. In return, they're given the chance to leave their problems behind and a blank slate to start their lives anew. But not everyone should be trusted, especially when they each have secrets of their own they'll do anything to protect..."--